Impact of the National Service Framework for coronary heart disease on treatment and outcome of patients with acute coronary syndromes. Issue 3 (20th May 2005) - Graham, J J; Timmis, A; Cooper, J; Ramdany, S; Deaner, A; Ranjadayalan, K; Knight, C
Abstract : Objectives: To evaluate the impact the National Service Framework (NSF) for coronary heart disease has had on emergency treatment and outcomes in patients presenting with acute coronary syndromes. Design: Retrospective cohort study. Setting: Coronary care units of two district general hospitals. Results: Data from 3371 patients were recorded, 1993 patients in the 27 months before the introduction of the NSF and 1378 patients in the 24 months afterwards. After the introduction of the NSF in-hospital mortality was significantly reduced (95 patients (4.8%) v 43 (3.2%), p  =  0.02). This was associated with a reduction in the development of Q wave myocardial infarction (40.6% v 33.3%, p < 0.0001) and in the incidence of left ventricular failure (15.9% v 12.3%, p  =  0.003). The proportion of patients receiving thrombolysis increased (69.4% v 84.7%, p < 0.0001) with a decrease in the time taken to receive it (proportion thrombolysed within 20 minutes 12.1% v 26.6%, p < 0.0001). The prescription of β blockers (51.9% v 65.8%, p < 0.0001), angiotensin converting enzyme inhibitors (37% v 66.4%, p < 0.0001), and statins (55.2% v 72.7%, p < 0.0001) improved and the proportion of patients referred for invasive investigation increased (18.3% v 27.0%, p < 0.0001). Trend analysis showed that improvements in mortality and thrombolysis were directly associated with publication of the NSF, whereas the improvements seen in prescription of β blockers and statins were the continuation of pre-existing trends. Conclusions: In the two years that followed publication of the NSF the initial treatment and outcome of patients presenting with acute coronary syndromes improved. Some of the improvements can be attributed to the NSF but others are continuations of pre-existing trends.